Neopyrenochaetopsis machili sp. nov. on Machilus nanmu from Shanxi Province, China - He, Yong-Ze (Phytotaxa, 2025)
During a survey of microfungi on symptomatic leaves from Machilus nanmu (Oliv.) Hemsl., an interesting anamorphic ascomycetous fungus was found. Based on morphological comparisons and phylogenetic analyses of four-locus (ITS, LSU, tub, and rpb2) proved that this fungus represented a new species of Neopyrenochaetopsis (Pyrenochaetopsidaceae), N. machili sp. nov. The detail morphological descriptions, phylogenetic tree and photographs are provided here.